2019
DOI: 10.21203/rs.2.16851/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The propionic acid and butyric acid in serum but not in feces are increased in patients with diarrhea-predominant irritable bowel syndrome

Abstract: Background & Aims : Short-chain fatty acids (SCFAs) play a pivotal role in maintaining homeostasis in humans. It might be involved in the pathogenesis of irritable bowel syndrome (IBS). Our study aims to explore the alteration of SCFAs in patients with diarrhea-predominant IBS (IBS-D). Methods: We recruited patients with IBS-D defined by Rome Ⅳ criteria and age-and-gender matched healthy controls (HCs). A headspace solid-phase microextraction gas chromatography–mass spectrometric (HS-SPME-GC-MS) method was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Therefore, as products of gut microbiota, SCFA level reflects the status of the microbiota. Moreover, in a recent study increased levels of propionate and butyrate in IBS-D in blood serum were discovered which corresponds to our data [ 42 ]. Hence, although it has been reported that fecal and mucosal microbiota are structurally diverse they are highly correlated [ 43 ], and can be used to discriminate between IBS-D subjects and healthy controls [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, as products of gut microbiota, SCFA level reflects the status of the microbiota. Moreover, in a recent study increased levels of propionate and butyrate in IBS-D in blood serum were discovered which corresponds to our data [ 42 ]. Hence, although it has been reported that fecal and mucosal microbiota are structurally diverse they are highly correlated [ 43 ], and can be used to discriminate between IBS-D subjects and healthy controls [ 44 ].…”
Section: Discussionsupporting
confidence: 92%